Use of Social Media for Health-Related Tasks by Adolescents With Inflammatory Bowel Disease: A Step in the Pathway of Transition. Issue 6 (18th May 2018) - Szeto, Winnie; van der Bent, Annelotte; Petty, Carter R; Reich, Jason; Farraye, Francis; Fishman, Laurie N
Abstract: Background: Social media is commonly used among the adolescent and young adult population, including those with chronic diseases. For adults, these platforms have been shown to be a major source of health information. Our aims were to explore how youth with inflammatory bowel disease (IBD) use social media for (1) disease information gathering, (2) provider communication, (3) sense of belonging to the IBD community, (4) self-expression around IBD, and (5) disease management/monitoring. Methods: An anonymous and voluntary survey was administered to IBD patients age 12 to 25 years at a single center over 4 months. Results: Of 218 patients approached, there were 109 respondents. The mean age of the cohort (SD) was 18 (2.9) years, 65% were male, and 82% had Crohn's disease. Almost all patients accessed the Internet daily, but only 17% reported looking up information about IBD "always" or "often." Less than half (47%) turned to medical websites (WebMD or Crohn's and Colitis Foundation) for information. A small number (16%) connected with other IBD patients. Patients' preferred communication with provider was by e-mail (88%) compared with a phone call to the office (67%) or hospital website/patient portal (52%). Few patients used mobile applications to monitor symptoms (2%) or for medication reminders (9%), although there was professed interest. Conclusions: Adolescents and young adults with IBD are less likely than adults to use social media for health-related activities. They prefer e-mail rather than oral communication between visits, and privacy seems to be less of a concern. Targeted education and skill building may be helpful for this transitioning population.